Glyoxal- and formaldehyde slant column densities measured during the cruise MSM58/2 over the Atlantic Ocean using MAX-DOAS - Lisa K Behrens; Andreas Hilboll; Andreas Richter; Enno Peters; Leonardo M A Alvarado; Anna Beata Kalisz Hedegaard; Folkard Wittrock; John Philipp Burrows; Mihalis Vrekoussis (PANGAEA, 2019)
Trace gas maps retrieved from satellite measurements show enhanced levels of the atmospheric volatile organic compounds formaldehyde (HCHO) and glyoxal (CHOCHO) over the Atlantic Ocean. To validate the spatial distribution of this continental outflow, ship-based measurements were taken during the Continental Outflow of Pollutants towards the MArine tRoposphere (COPMAR) project. A Multi-AXis Differential Optical Absorption Spectrometer (MAX-DOAS) was operated aboard the research vessel (RV) Maria S. Merian during cruise MSM58/2. This cruise was conducted in October 2016 from Ponta Delgada (Azores) to Cape Town (South Africa), crossing between Cabo Verde and the African continent. The instrument was continuously scanning the horizon, looking towards the African continent. Enhanced levels of HCHO and CHOCHO were found in the area of expected outflow during this cruise. The observed spatial gradients of HCHO and CHOCHO along the cruise track agree with the spatial distributions from satellite measurements and the Model for OZone and Related chemical Tracers version 4 (MOZART-4) model simulations. The continental outflow from the African continent is observed in an elevated layer, higher than 10000.167emm, and probably originates from biogenic emissions or biomass burning according to FLEXible PARTicle dispersion model (FLEXPART) emission sensitivities.
Supplement to: Behrens, LK et al. (2019): Detection of outflow of formaldehyde and glyoxal from the African continent to the Atlantic Ocean with a MAX-DOAS instrument. Atmospheric Chemistry and Physics, 19(15), 10257-10278, https://doi.org/10.5194/acp-19-10257-2019